Weak magnetic transitions in pyrochlore Bi2Ir2O7 - Baker, P; Moeller, J; Pratt, F; Hayes, W; Blundell, S; Lancaster, T; Qi, T; Cao, G (2013)
Muon spin relaxation measurements on Bi2Ir2O 7 show that it undergoes a bulk magnetic transition at 1.84(3) K. This is accompanied by increases in the muon spin relaxation rate and the amplitude of the nonrelaxing part of the signal. The magnetic field experienced by muons is estimated to be 0.7 mT at low temperature, around two orders of magnitude smaller than that in other pyrochlore iridates. These results suggest that the low-temperature state represents static magnetism of exceptionally small magnetic moments, ∼0.01μB/Ir. The relaxation rate increases further below 0.23(4) K, coincident with an upturn in the specific heat, suggesting the existence of a second low-temperature magnetic transition. © 2013 American Physical Society.